Place meaning and consistency with offshore wind: An island and coastal tale. (October 2020) - Russell, Aaron; Firestone, Jeremy; Bidwell, David; Gardner, Meryl
Abstract: This work continues a series of analyses using surveys of local communities regarding the Block Island Offshore Wind Project. Data collection focused on island and coastal resident attitudes toward the project and cognitions of the coastal setting. We report results from the first and final surveys. Multivariate statistical analysis was used to evaluate relationships among variables. Results indicate that attitudes about the project have solidified as more people have seen it. A majority support the project, and a small percent consider the project inconsistent with specific meanings associated with the ocean environment. These meanings stand out amongst other place constructs. Furthermore, the relationship among turbine descriptions and place meanings and their consistency with the project as a use of the ocean, along with general support for the project is explored. The results continue to validate a place-based understanding of the responses of people to a changing energy landscape. Highlights: Support for the Block Island Offshore Wind Project is high. Island (near) residents show more firm support than Coastal residents. Place meanings such as aesthetic beauty and family and community identity resonate. Differences include pristineness vs. recreational enjoyment between the populations. Turbine appearance and fit within the landscape are correlated with project support.